Exploring Teachers Techniques in Teaching Speaking - Fakhria Mega Alfallah; Hilda Puspita; Azhar Aziz Lubis (Journal of English Education and Teaching, 2023)
The objectives of this research were to find out the types of techniques in teaching speaking and to describe how the teachers implement the teaching speaking techniques at SMA 6 Kota Bengkulu. This research used a case study qualitative method. The population of the research was two teachers who taught the first-grade students of SMA 6 Kota Bengkulu. To collect the data, the researcher used observation, interview, and documentation. Data processing was divided into three stages, those are data reduction, displaying data, and conclusion. The result of the research showed that teachers used some techniques in teaching speaking, such as discussion, storytelling, and brainstorming. In the discussion, the teacher asked students to make a group consisted of two people because students in the class were just half of the total of students. In storytelling, the teacher told her stories when she was a student to motivate students in learning. In brainstorming, the teacher began the lesson by giving a question to make students think and got ideas. It is concluded that teachers used techniques adjust with the material and condition of the class. It is recommended for further researchers in conducting the same topic about speaking technique.